The Analysis Quintuple Helix Minicont as a challenge for Future Logistics Defense - Ghazalie, Ghazalie (Advances in Social Sciences Research Journal, 2020)
In supporting competition areas, the International Trade and many kinds of free trade agreements in many industries will become progressively stringent. The implementation of the ASEAN Economic Community increases the need to grow the competitiveness of domestic industries through developing the performance of its logistics system. The Logistic Report Index 2018 was released by the World Bank Indicated that Indonesia rank was in 46th position out of 160 countries. Indonesia will definitely not be able to compete with their ASEAN peers if the development of infrastructure is still poor and logistics cost is higher than another countries. Thefore Indonesia is innovating Minicont-Mini Shipping Container which cutt off by up to 30% logistics cost and potentially become the next logistic defense. By applying quintuple helix this research is to analyze how Minicont can cut off logitisct cost significantly and support logistic defense in the future. The researchers apply descriptive method for data analysing and the result proved that Minicont shorten supply chain process.